2005
DOI: 10.1088/0957-4484/17/1/039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic length scales of nanosize zinc ferrite

Abstract: Nanosize zinc ferrite samples with an average particle size of 6–65 nm were prepared by a new chemical reaction involving nitrates of Zn and Fe and investigated for magnetic behaviour and defect structure. The sample with an average particle size of 6 nm has considerable inversion in cation distribution as shown by its hysteresis loop and increased magnetization. Mössbauer spectroscopy gives a single doublet for all the samples. Mössbauer parameters like quadrupole splitting and linewidth change sharply as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
50
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 19 publications
11
50
0
2
Order By: Relevance
“…In agreement with previous studies [17,18] we observed that the absorption area increases for ZM and ZS compare to that of ZC. It is well known that area of the curve is a measure of recoil free fraction.…”
supporting
confidence: 93%
“…In agreement with previous studies [17,18] we observed that the absorption area increases for ZM and ZS compare to that of ZC. It is well known that area of the curve is a measure of recoil free fraction.…”
supporting
confidence: 93%
“…Nanosized magnetoelectric material causes superparamagnetic relaxation contribute to least the hysteresis than ferromagnetic. 29 The enhancement in ferromagnetic properties is due to the smaller particle size in our specimen.…”
Section: +mentioning
confidence: 88%
“…But, due to the degree of inversion, which is large for smaller size particles, intersublattice (A-B) super-exchange interactions in smaller size particles occur to a greater extent than in larger size particles. Hence, saturation magnetization increases for smaller size particles [31], using Mossbauer's experiment, showed that the degree of inversion is large in the case of smaller size particles. Also, an impure α-Fe 2 O 3 phase was detected by XRD (Figure 2(a)), the heating rate of calcinations and the surface spin structure can be an influence that increases the saturation magnetization in smaller size particles [18].…”
Section: Phase Composition and Morphology Of Precursors Andmentioning
confidence: 98%